INSECURITY, INFLATION AND SUSTAINABILITY OF SMALL AND MEDIUM ENTERPRISE IN NIGERIA - Kolade Akinpelu Ayobami; ABIODUN-AFOLABI FADEKEMI OMOGBONJUBOLANLE; ABEY SAMUEL TAIWO; OYEDOKUN GODWIN EMMANUEL (International Journal of Social Sciences and Management Review, 2024)
This study examined the impact of insecurity and inflation on the sustainability of Small and Medium Enterprises (SMEs) in Nigeria from 2008 to 2023. Using time-series data obtained from the National Bureau of Statistics and the Global Terrorism Index, the research focuses on three key variables: SME growth (SMES_G), insecurity (INS), and inflation rate (INF). A quantitative research approach is employed, utilizing E-views version 10 for data analysis, including descriptive statistics, correlation analysis, and multiple linear regressions. The Augmented Dickey-Fuller (ADF) unit root test is conducted to assess the stationarity of the data. The results reveal that insecurity has a significant negative impact on SME growth, with a regression coefficient of 5.1759, indicating that an increase in insecurity corresponds to a 51% decline in sustainability. Additionally, inflation shows a significant adverse effect on SME growth with a coefficient of -0.0404. The Jarque-Bera test confirms the normality of the residuals, ensuring the validity of the regression results. The findings support the hypothesis that insecurity significantly hampers the sustainability of SMEs in Nigeria, highlighting the need for improved security measures to create a conducive environment for business growth. This research underscores the critical role of security in promoting SME sustainability and calls for government intervention to address the rising insecurity that threatens socio-economic development in Nigeria. Recommendations include enhanced security measures, job creation, and strengthening intelligence and counter-terrorism strategies.
Keywords: Insecurity; Inflation Sustainable entrepreneurship; SMEs growth; Nigeria